Heritage for education purposes: A case study of Taxila valley - Khan, Muhammad Ashraf (Centre for Heritage Studies, University of Kelaniya, Kelaniya, Sri Lanka., 2019)
Pakistan is a land of rich cultural heritage. It has an impressive architectural legacy spreading over a vast area and long tradition covering several periods from Mehr Garh to Indus Civilization and even to Gandhara Civilization. The educational contributions of Gandhara Civilization distinct it among other civilizations of the ancient world. This paper presents the case study of Taxila Valley, which is the cradle of Gandhara (Budhist) Civilization flourished during the Kushana period. It presents the glorious Buddhist Stupas and Monasteries wherein monks from far and wide would come to Julian (center of learning) for seeking education. It was the first university in South Asia wherein scholar like Panini (Sansikrat Philologist &Grammarian) and Kautaliya taught history and philosophy. It is here that the Brahmin princes and students migrated from distance to enroll at Taxila and its alumni include, Givak, Parasasenajit and Charaka, a famous physician. This treasure of knowledge embedded in Gandhara heritage can be transferred to new generation through involvement of school and college students. They can be encouraged to conduct excavations, arrange field trips to the heritage sites. It can be promoted through digitalization of artifacts, organizing workshops and frequent visits to museums. It will result in awareness of educational significance of culture and heritage through education, including all aspects of environment setting.
Keywords: Gandhara, Buddhist, Civilization, Heritage, Education, Stupa, Monastery